Bridge over the Snake River, Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Shows two men in a rowboat on the river, buildings and boats along the shore. Caption on image: "Bridge over Snake River, Nome, Alaska" Original image in Hegg Album 38, page 16. Original photograph by Eric A. Hegg 1363; copied by Webster and Stevens 307.A.